Interest rate convergence among some selected Caribbean economies - Modeste, Nelson (2003)
Looks at the convergence of the deposit rate and the lending rate among the economies of Barbados, Trinidad and Tobago, Jamaica, Guyana, and the seven Organization of Eastern Caribbean States. Concludes that more competition among banks for bank deposits should be promoted on a regional basis as a means of further enhancing the linkage of bank deposits rates regionally.